2020
DOI: 10.1016/j.ijid.2019.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and phylogenic analysis of human respiratory syncytial virus in patients with respiratory infections during 2011–2016 in southern China

Abstract: A B S T R A C TBackground: Human respiratory syncytial virus (RSV) is one of the most important pathogens that cause acute respiratory infections in children and immunocompromised adults. This work was conducted to understand the epidemiological and phylogenetic features of RSV in southern China during 2011-2016. Methods: A total of 16 024 nasopharyngeal swabs were collected from patients with respiratory infections in 14 hospitals, and screened for RSV and seven other respiratory viruses using real-time PCR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
22
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 30 publications
13
22
4
Order By: Relevance
“…Studies conducted in temperate climates and RSV, such as in Korea, have reported to be prevalent between October and April [ 15 17 ]. Compared with similar studies in China over a similar period, the results do not show as clear alternating pattern [ 18 ].…”
Section: Discussioncontrasting
confidence: 84%
“…Studies conducted in temperate climates and RSV, such as in Korea, have reported to be prevalent between October and April [ 15 17 ]. Compared with similar studies in China over a similar period, the results do not show as clear alternating pattern [ 18 ].…”
Section: Discussioncontrasting
confidence: 84%
“…Specifically, with this lab testing data a transition from RSV-B to RSV-A was observed between the 2016 and 2017 seasons in WA (data not shown). These results are consistent with other molecular epidemiological studies globally that show both RSV-A and RSV-B subtypes co-circulate with shifting predominance across seasons (Di Giallonardo et al, 2018; Luo et al, 2020; Razanajatovo Rahombanjanahary et al, 2020; Yun et al, 2020)…”
Section: Resultssupporting
confidence: 92%
“…Specifically, a transition from RSV-B to RSV-A was observed between the 2016 and seasons in WA (data not shown). These results are consistent with other molecular epidemiological studies globally that show both RSV-A and RSV-B subtypes co-circulate with shifting predominance across seasons [7,[31][32][33] were generated in a previous study [7].…”
Section: Resultssupporting
confidence: 92%
“…The majority of ARTI cases can be attributed to viral infection, and among the diverse types of respiratory viruses, respiratory syncytial virus (RSV), adenovirus (ADV), influenza virus (Flu), and parainfluenza virus (PIV) are the most common ones. [ 2 5 ] According to World Health Organization statistics, RSV infection causes the hospitalization of 3.2 million people, and 1/15th of them eventually die. [ 6 ] Flu exhibits an obvious seasonality in positive infection rates and accounts for 7% of ARTI cases, 5% of ARTI-related hospital admissions, and 4% of ARTI-related deaths in children <5 years.…”
Section: Introductionmentioning
confidence: 99%